Just breathe - Wiggs, Susan (Don Mills, Ont. : Mira, 2008)
When cartoonist Sarah Moon is faced with the unthinkable infidelity of her cancer survivor husband, she returns home to Chicago, where she discovers that unexpected change and an old flame can be like a breath of fresh air for both her body and soul.
Keywords: Women cartoonists -- Fiction; Adultery -- Fiction; Marital conflict -- Fiction; Man-woman relationships -- Fiction; Love stories